Pengaruh Sistem Informasi Akuntansi, E - Commerce, dan Media Sosial terhadap Keputusan untuk Berwirausaha - Adinda Yunita Siswananti (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2024)
Information technology is very important for business, including accounting information systems. One way businesses use information technology to increase their competitiveness is e-commerce. Additionally, social media helps in implementing online marketing strategies. The aim of this research is to evaluate and analyze the impact of accounting information systems, e-commerce and social media on decisions made by entrepreneurs. This type of research is quantitative and uses an accidental sampling method to produce 230 respondents. This research collects data by distributing questionnaires on the network using Google Form, and data analysis is carried out using the SmartPLS SEM application for quantitative analysis. The conclusion of the t test shows that accounting information systems, e-commerce, and social media have a positive and significant impact on decisions made by entrepreneurs.